A STUDY ON CAPRINE PNEUMONIA IN IRAQI LOCAL GOATS ETIOLOGICAL FINDINGS - H. Al-Joboury , K.; M. Al-Darraji , A. (The Iraqi Journal of Veterinary Medicine, 1989)
In a study designed to evaluate the prevalence of caprine pneumonia and to identify it's bacterial and parasitic causes, 100 lungs with pneumonic lesions were collected. The prevalence rate was 12.5%. The most commonly associated bacterial isolates with the suppurative and interstitial pneumonia were the followings: Staphylococcus aureus and Streptococcus haemolyticus (x,B), while the most commonly associated bacterial isolates with fibrinous and fibrino - purulent pneumonia was Pasteurella haemolytica. The most commonly associated parasite in chronic purulent and muco purulent pneumonia was Dictyocaulus filaria, in cases of chronic interstitial pneumonia were either D. filaria or Muellerius capillaris and in cases of chronic granulomatous pneumonia were a combination of D. filaria and M. capillaris. Four miscellaneous parasitic lung lesions were reported, three of which were hydatid cysts (Echinococcus granulosus) and the fourth one was due to liver fluke (Fasciola gigantica).